Pengaruh Brand Credibility dan Brand Prestige Terhadap Purchase Intention Pada Produk Handphone Oppo di Kota Mataram - Alayda Salsabila; M. Ilhamuddin (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2025)
This research aims to determine the effect of brand credibility and brand prestige on consumers' purchase intention for Oppo mobile phone products in Mataram City. In an era of increasingly tight market competition, trust and brand image become important elements in shaping consumer buying interest. This research uses a quantitative method with a causal associative approach. A sample of 100 respondents was selected using purposive sampling technique, specifically individuals who are familiar with Oppo products and are over 18 years old. Data collection was carried out through questionnaires using a Likert scale, and data analysis involved validity tests, reliability tests, classical assumption tests, multiple linear regression, as well as F tests and t tests. The research results show that brand credibility and brand prestige have a positive and significant effect on purchase intention both simultaneously and partially. The adjusted R² value of 0.468 indicates that the two independent variables can explain 46.8% of the variation in purchase intention. This finding implies that strategies to enhance brand credibility and prestige are important in driving consumer purchase decisions for Oppo smartphone products in the local market.